Thermal Ablation of Stage I Non-Small Cell Lung Carcinoma - Ridge, Carol A.; Solomon, Stephen B.; Thornton, Raymond H. (Seminars in Interventional Radiology, 2014)
Ablation options for the treatment of localized non-small cell lung carcinoma (NSCLC) include radiofrequency ablation, microwave ablation, and cryotherapy. Irreversible electroporation is a novel ablation method with the potential of application to lung tumors in risky locations. This review article describes the established and novel ablation techniques used in the treatment of localized NSCLC, including mechanism of action, indications, potential complications, clinical outcomes, postablation surveillance, and use in combination with other therapies.
Keywords: ablation techniques; carcinoma; non-small cell lung; tomography; x-ray computed; positron emission tomography; radiology; interventional radiology